A resiliência nos empreendedores egressos do Banco do Brasil - Cangussu, Ewerton Taveira (2008)
This study seeks to understand the process of resilience by means of experience accounts of entrepreneurs who used to work at the Brazilian Bank and took part in a voluntary dismissal program. Resilience refers to a human ability that is very relevant in the struggle against life adversities. In the field of entrepreneurship, difficulties and confrontations with striking events often occur. The strategy designed for the accomplishment of this study comprises a descriptive qualitative and phenomenological research as to unveil such experiences. Data analysis was done with the Cycle of the comprehensive explanatory analysis of phenomenological research. Results show that the experience reports of the subjects clearly indicate resilient behavior and the presence of processes indicative of resilience.